Hadith #874 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
The Messenger of Allah (may peace he upon him) used to touch our shoulders in prayer and say: Keep straight, don’t be irregular, for there would be dissension in your hearts. Let those of you who are sedate and prudent be near me, then those who are next to them, then those who are next to them. Abu Mas’ud said: Now-a-days there is much dissension amongst you.
Grade: Sahih

Hadith #946 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
A person came to the Messenger of Allah (ﷺ) and said: I keep away from the morning prayer on account of such and such (a man), because; he keeps us so long. I never saw God’s Messenger (ﷺ) more angry when giving an exhortation than he was that day. He said: 0 people, some of you are scaring people away. So whoever of you leads the people in prayer he must be brief, for behind him are the weak, the aged, and the people who have (argent) business to attend.
Grade: Sahih

Hadith #1427 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
The one who is most versed in Allah’s Book should act as Imam for the people, but If they are equally versed in reciting it, then the one who has most knowledge regarding Sunnah if they are equal regarding the Sunnah, then the earliest one to emigrate; it they emigrated at the same time, then the earliest one to embrace Islam. No man must lead another in prayer where (the latter) has authority, or sit in his place of honour in his house, without his permission. Ashajj in his narration used the
Grade: Sahih

Hadith #1429 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
The Messenger of Allah (ﷺ) said to us: The one who is well grounded in Allah’s Book and is distinguished among them in recitation should act as; Imam for the people. and if they are equally versed in reciting it, then the one who has most knowledge regarding Sunnah; if they are equal regarding the Sunnah, then the earliest one to emigrate; If they emigrated at the same time, then the oldest one in age. No man must lead another in prayer in latter’s house or where (the latter) has authority
Grade: Sahih

Hadith #1772 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
If anyone recites the two verses at the end of Surah al-Baqara at night, they would suffice for him ‘Abd al-Rahman said: I met Abu Mas’ud and he was circumambulating the House (of Allah) and asked him about this (tradition) and he narrated it to me from the Messenger of Allah (ﷺ).
Grade: Sahih

Hadith #2001 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
Verily the sun and the moon are the two signs among the signs of Allah by which He frightens his servants and they do not eclipse on account of the death of any one of the people. So when you see anything about them, observe prayer, supplicate Allah till it is cleared from you.
Grade: Sahih

Hadith #2002 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
Verily the sun and the moon do not eclipse on account of the death of any one of the people, but they are the two signs among the signs of Allah. So when you see it, stand up and observe prayer.
Grade: Sahih

Hadith #2206 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
When a Muslim spends on his family seeking reward for it from Allah, it counts for him as sadaqa.
Grade: Sahih

Hadith #2239 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
We were commanded to give charity (despite the fact.) that we were coolies. Abu ‘Aqil donated half a sa’. And there came another man with more than this. The hypocrites said: Verily Allah does not stand in need of the charity of this, and the second one has done nothing but only made a show (of his charity). Then this verse was revealed.” Those who scoff at the voluntary givers of charity among the believers as well as those who cannot find anything (to give) but with their hard labour”
Grade: Sahih

Hadith #3868 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
A person from people who lived before you was called to account (by Allah at the Day of Judgment) and no good was found in his account except this that lie being a rich man had (financial) dealings with people and had commanded his servants to show leniency to the straitened ones. Upon this Allah, the Exalted and Majestic, said: We have more right to this, so overlook (his faults).
Grade: Sahih

Hadith #4178 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
When I was beating my servant, I heard a voice behind me (saying): Abu Mas’ud, bear in mind Allah has more dominance over you than you have upon him. I turned and (found him) to be Allah’s Messenger (ﷺ). I said: Allah’s Messenger, I set him free for the sake of Allah. Thereupon he said: Had you not done that, (the gates of) Hell would have opened for you, or the fire would have burnt you.
Grade: Sahih

Hadith #4179 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
I seek refuge with Allah, but he continued beating him, whereupon he said: I seek refuge with Allah’s Messenger, and he spared him. Thereupon Allah’s Messenger (ﷺ) said: By Allah, God has more dominance over you than you have over him (the slave). He said that he set him free.
Grade: Sahih

Hadith #4762 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
It is (offered) in the way of Allah. The Messenger of Allah (ﷺ) said: For this you will have seven hundred she-camels on the Day of Judgment all of which will be muzzled.
Grade: Sahih

Hadith #4764 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
A man came to the Messenger of Allah (ﷺ) and said: My riding beast has been killed, so give me some animal to ride upon. He (the Holy Prophet) said: I have none with me. A man said: Messenger of Allah, I can guide him to one who will provide him with a riding beast. The Messenger of Allah (ﷺ) said: One who guides to something good has a reward similar to that of its doer.
Grade: Sahih

Hadith #5172 - Sahih Muslim - Abu Mas'ud al-Ansari (Sahih Muslim)
0 ye, prepare for us food sufficient for five persons, for I intend to invite Allah’s Apostle (ﷺ) who would be the fifth amongst the five. He (the narrator) reported that he then prepared the food and came to Allah’s Apostle (ﷺ) and invited all the five (including him) who was the fifth amongst them to the feast. A man followed him and when Allah’s Apostle (ﷺ) reached the door, he said: This man has followed us; if you like you may permit him (to join the meal) and if you like he can
Grade: Sahih